GENETIC DIVERSITY IN SODIUM AZIDE-INDUCED BARLEY MUTANT LINES - B. Dyulgerova; N. Dyulgerov (Trakia Journal of Sciences)
The aim of this study was to assess the diversity among sodium azide-induced mutants of winter 2-rowed barley for 8 quantitative traits of by multivariate analyses. Forty-seven mutant lines and their parental varieties Kuber, Zagorets, Asparuh, and Imeon were tested in complete block design with four replications. The studied traits included spike length, awn length, peduncle length, spikelet and grain number per spike, grain weight per spike, 1000 grain weight and grain yield. Principal component and cluster analyses were used for the assessment of mutants. Traits spike length, spikelet number per a spike, grain number per spike and grain weight per spike had the largest contribution to the divergence between mutants. The cluster and principal component analyses employed in the present study divided the mutant lines into different groups, which were deviated significantly from the respective parents. Diverse mutant lines with improved yield-related traits suitable for including in winter barley breeding program were identified.